A Method for Improving the Technique for the Synthesis of Quasi-two Bandpass Matching Devices - M. A. Yantsevich; A. A. Sviridenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The article deals with issues related to the possibilities of the analytical technique for the synthesis of quasi-two-band matching devices and the way to improve it. The technique is based on the mathematical apparatus of the Generalized Darlington method with the use of a special method of forming quasi-two-band frequency characteristics at the stage of choosing an approximating function. A comparison of the results of load matching obtained using the developed methodology and a progressive numerical synthesis method is presented. The analysis of the solved problem allowed us to make a private assessment of the capabilities of the proposed analytical method of matching. An important limiting circumstance for the synthesis technique is indicated – the lack of solutions for loads of increased complexity, which is caused by a small variability of the known approximating power transfer functions. As a solution to the problem, boundedly flat functions are considered, which differ from classical approximations in their extended variability. The use of a combination of knowledge about the formation of quasi-two-band frequency characteristics and the technique of using limited-flat functions made it possible to expand the range of matched loads. A solution to the test problem of matching a 5-element load is presented, for which the use of classical approximations is not acceptable.